Tafsit Tematik Pendidikan Tentang Kelemahan dalam Diri Manusia - Nurhadi, Nurhadi (MASALIQ, 2022)
Allah swt sent down the Qur'an to be read with full appreciation (Tadabbur), believe in its truth and try to practice it. Al-Qur'an is the source of Islamic teachings related to the totality of human life. The search for the meaning of the scriptures is reflected in various studies, both textually and contextually and even in the form of a synthesis of an academic discipline. Regarding the verse about human weakness, it is found in the suras al-Ma'arij, al-Rum and Yasin. The thematic interpretations are as follows: 1). Al-Ma'arij's interpretation (70): 19-27: Humans are very weak compared to the power of Allah swt, because: (1). Man was created to be grouchy and miserly; (2). Except for those who pray and istiqomah; (3). Also people who like to give sodaqah to beggars and the poor; (4). And those who believe in the reward of good in heaven and evil with the punishment of hell; (5). There are three cures for complaining and miserly diseases: First, maintaining consistency in performing prayers; Second, willing and willing to donate wealth to people in need; Third, believe in and believe in the day of vengeance. 2). Al-Rum (30): 54: As creatures created by Allah swt we should as servants always be grateful and always remember that we will not live forever (eternal) because eternal life is life in the hereafter. 3). Yasin (36): 77: This noble verse in it mentions the doubts of those who deny the resurrection and the answer. Those who deny the resurrection and doubt it. Then Allah changed his situation little by little so that he became a strong figure.